New species of Loandalia (Polychaeta: Pilargidae) from Queensland, Australia - Marks, Shona; Hocknull, Scott (Zootaxa, 2006)
Two new species of Loandalia are described from Queensland, Australia. Loandalia fredrayorum sp. nov. is described from Moreton Bay, south eastern Queensland and is distinguished from all other species of Loandalia by the presence of singular palpostyles; uniramous parapodia at chaetiger 1; an emergent notopodial spine at chaetiger 9; neurochaetae numbering 20–24; ventral cirri begin on chaetiger 7 and the pygidium with two lateral papillae-like anal cirri. Loandalia gladstonensis sp. nov. is described from Gladstone Harbour, central eastern Queensland and is distinguished from all other species of Loandalia by the presence of bifid palpostyles; chaetiger 1 uniramous with remaining chaetigers biramous; an emergent notopodial spine from chaetiger 7–8; ventral cirri present from chaetiger 5 and neurochaetae numbering 5–6.